Digital Archives of Islam Nusantara: Preserving Manuscripts, Oral Traditions, and Local Saints’ Cults in the Age of Platform Capitalism - Nurfatsyah Zein, Khumaedi (Islamic Civilization and History, 2025)
Background: Platform capitalism introduces commercial imperatives that reshape Islamic heritage through algorithmic curation, monetization mechanisms, and data extraction, potentially reproducing colonial power structures in digital preservation.Objective:This study examines how Islam Nusantara heritage communities navigate platform capitalism while maintaining cultural sovereignty and epistemic justice.Method:A qualitative multi-case study combined with digital ethnography analyzed 56 digital archiving initiatives across Indonesia, Malaysia, and Singapore through 47 semi-structured interviews and systematic platform observation during 2023–2024.Findings and Implications:Findings reveal three strategic responses: pragmatic accommodation (67% strategic essentialism), active resistance (89% platform pluralism), and alternative infrastructure development using community-owned repositories. Platform mechanisms transform heritage through algorithmic optimization requiring content compression and sensationalization. Indigenous Data Sovereignty-inspired governance models achieve the highest epistemic justice scores (4.7/5) compared to institutional repositories (2.3/5) and platform-mediated models (1.7/5). The research contributes a decolonial digital heritage governance framework emphasizing community-controlled metadata standards, CARE Principles adaptation for Islamic contexts, and policy recommendations for platforms, governments, and international heritage organizations to support community data sovereignty.Conclusion:The study demonstrates that while platform capitalism reshapes Islamic digital heritage through algorithmic and commercial logics, community-driven governance models grounded in data sovereignty provide more equitable and epistemically just pathways for digital preservation.